Interfacial debonding and slipping of carbon fiber-reinforced ceramic-matrix composites under two-stage cyclic loading. Issue 5 (13th June 2017) - Li, L. B.
Abstract: In this paper, the interface debonding and frictional slipping of carbon fiber-reinforced ceramic-matrix composites (CMCs) under two-stage cyclic fatigue loading have been investigated using micromechanics approach. Under cyclic fatigue loading, the fiber/matrix interface shear stress degrades with increasing cycle number due to interface wear. The synergistic effect of interface wear and fatigue loading sequence on interface debonding and frictional slipping has been analyzed. Based on the fatigue damage mechanism of fiber slipping relative to matrix, in the interface debonded region, upon unloading and subsequent reloading, the interface debonded length and interface slip lengths, i.e. interface counter-slip length and interface new-slip length, are determined using the fracture mechanics approach. The relationships between interface debonding, interface slipping, interface wear, cycle number, and different loading sequences are determined. There are two types of fatigue loading sequences considered, i.e. (1) cyclic loading under low peak stress for N 1 cycles, and then high peak stress; and (2) cyclic loading under high peak stress for N 1 cycles, and then low peak stress. The effects of peak stress level, interface wear, cycle number, and loading sequence on interface debonding and frictional slipping of fiber-reinforced CMCs have been analyzed. The fatigue hysteresis loops of cross-ply carbon fiber-reinforced silicon carbide composite corresponding to different cycle number under two-stage cyclic fatigue loading have been predicted.